Water-repellent paint

JP2026166138APending Publication Date: 2026-10-14OSAKA GAS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025058908
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0019】 本発明は、新たに、撥水性塗料を提供する事が出来る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166138000001
    Figure 2026166138000001
Patent Text Reader

Abstract

An object of the present invention is to newly provide a water-repellent coating material. [Solution] A water-repellent coating material comprising (A) a Ti compound, (B) a fluorine-free Si compound, and (C) a solvent, wherein the (A) Ti compound has an average primary particle diameter of 1 nm to 50 nm, and the (B) fluorine-free Si compound is a compound represented by the following formula (1), CH3-(CH2)a-Si(R 1 )(R 2 )(R 3 )(1) (In formula (1), a represents an integer of 3 to 30. In formula (1), R 1 , R 2 , and R 3 are identical or different, and each independently represents a hydrogen atom, an optionally substituted alkyl group, or an optionally substituted alkoxy group.) The (C) solvent is at least one solvent selected from the group consisting of water and alcohols, the water-repellent coating material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a water-repellent coating. [Background technology]

[0002] Patent Document 1 discloses a water-repellent and oil-repellent coated article obtained by coating with a coating composition comprising an alcohol, an alkoxysilane, a perfluoroalkylsilane, silica fine particles, a catalyst that promotes the hydrolysis reaction of an alkoxysilane, and water, wherein the mean square roughness (RMS) value on the surface of the article is 100 nm or more.

[0003] Patent Document 2 discloses a titania-coated silver composition comprising (A) titania-coated silver, (B) a Si compound, and (C) a solvent, wherein the amount of silver contained in the titania-coated silver composition is 0.01% to 25% by mass relative to the titanium oxide in the titania compound, the ratio of the average primary particle diameter of silver (Ag) nanoparticles to the average primary particle diameter of the titania compound contained in (A) titania-coated silver (average primary particle diameter of silver (Ag) nanoparticles / average primary particle diameter of titania compound) is 2 to 100, the surface of the silver (A) titania-coated silver is coated with the titania compound on 1% to 99% of the surface of the silver (Ag) nanoparticles, and the (B) Si compound is a hydrolysis product of an alkoxysilane. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2010-089373 [Patent Document 2] Patent No. 7574486 [Overview of the project] [Problems that the invention aims to solve]

[0005] The present invention aims to provide a new water-repellent coating. [Means for solving the problem]

[0006] TiO2 possesses photocatalytic activity and exhibits a photocatalytic effect in ultraviolet light environments, making it a material that can be applied in various situations, such as stain-resistant coatings for wallpaper, deodorizing coatings for automobiles, and hydrogen generation catalysts.

[0007] Paints containing titania typically exhibit hydrophilicity and are often used in hydrophilic applications. However, for applications such as stain resistance, paints containing titania with water-repellent properties are required. In recent years, from a hygiene perspective, paints containing titania with antibacterial and antiviral properties have also become in demand.

[0008] Traditionally, water-repellent coatings have used fluorine-containing Si compounds such as perfluoroalkylsilanes to achieve water repellency. However, in recent years, with the trend towards PFAS regulations, there is a demand for coating materials that do not contain fluorine materials in the system.

[0009] The present invention encompasses the following water-repellent coatings.

[0010] Section 1. It is a water-repellent paint, (A)Ti compound and (B) Si compounds that do not contain fluorine, (C) Contains a solvent, The (A)Ti compound has an average primary particle diameter of 1 nm to 50 nm. The aforementioned (B) fluorine-free Si compound is a compound represented by the following formula (1): CH3-(CH2) a -Si(R 1 )(R 2 )(R 3 ) (1) (In equation (1), a represents an integer between 3 and 30.) In formula (1), R 1 , R 2 , and R 3are the same or different and each independently represent a hydrogen atom, an optionally substituted alkyl group, or an optionally substituted alkoxy group.) The (C) solvent is at least one solvent selected from the group consisting of water and alcohols, A water-repellent coating material.

[0011] Item 2. The water-repellent coating material according to Item 1, further comprising (D) a hydrolysis product of an alkoxysilane.

[0012] Item 3. The water-repellent coating material according to Item 1, further comprising (E) silver.

[0013] Item 4. The water-repellent coating material according to any one of Items 1 to 3, wherein the water-repellent coating material has a water contact angle of 130° or more after being applied to a glass substrate.

[0014] Item 5. In the water-repellent coating material, The content of the (A) Ti compound is 0.01 mass% to 5 mass%, The content of the (B) fluorine-free Si compound is 0.01 mass% to 20 mass%, The water-repellent coating material according to any one of Items 1 to 3 above.

[0015] Item 6. The water-repellent coating material according to Item 2, wherein the hydrolysis product of the (D) alkoxysilane is a hydrolysis product of tetraethyl orthosilicate (TEOS).

[0016] Item 7. An antibacterial and antiviral coating liquid comprising the water-repellent coating material according to any one of Items 1 to 3 above.

[0017] Item 8. A method for producing the water-repellent coating material according to any one of Items 1 to 3 above, the method comprising: (1) a step of synthesizing a Ti compound in a solvent, introducing an organic chain to the Ti compound, and then producing titania-coated silver, and (2) After step (1), the titania-coated silver to which the organic chain is attached, a fluorine-free Si compound and an alkoxysilane are mixed in a solvent, and then the fluorine-free Si compound and the alkoxysilane are hydrolyzed. A method for manufacturing water-repellent coatings, including [the specified element].

[0018] The water-repellent coating of the present invention is a non-fluorine-based coating having a high water-repellent coating with a contact angle of 130° or more. [Effects of the Invention]

[0019] This invention makes it possible to provide a new water-repellent coating. [Modes for carrying out the invention]

[0020] The present invention will be described in detail below.

[0021] The embodiments illustrating the present invention are intended to provide a better understanding of the invention's intent and, unless otherwise specified, do not limit the scope of the invention.

[0022] In this specification, "contains" and "include" are concepts that encompass all of "comprise," "consist essentially of," and "consist of."

[0023] In this specification, when a numerical range is indicated as "A to B", it means "greater than or equal to A and less than or equal to B".

[0024] In this specification, when using indications such as parts, percentages, etc., they represent parts by mass, parts by weight, mass%, or weight% (wt%).

[0025] [1] Water-repellent paint TiO2 possesses photocatalytic activity and exhibits a photocatalytic effect in ultraviolet light environments, making it a material that can be applied in various situations, such as stain-resistant coatings for wallpaper, deodorizing coatings for automobiles, and hydrogen generation catalysts.

[0026] Paints containing titania usually exhibit hydrophilicity and are often used in hydrophilic applications, and in applications such as antifouling, paints containing titania having water repellency are demanded. In recent years, from the perspective of hygiene awareness, paints containing titania imparted with antibacterial and antiviral properties are also demanded.

[0027] Against the backdrop of recent PFAS regulatory trends, coating materials that contain no fluorine materials in the system are demanded.

[0028] The water-repellent paint of the present invention comprises: (A) a Ti compound, (B) a fluorine-free Si compound, and (C) a solvent,[[-END]] wherein the Ti compound (A) has an average primary particle diameter of 1 nm to 50 nm, the fluorine-free Si compound (B) is a compound represented by the following formula (1), CH3-(CH2) a -Si(R 1 )(R 2 )(R 3 ) (1) (In formula (1), a represents an integer of 3 to 30. In formula (1), R 1 , R 2 , and R 3 are identical or different, and each independently represents a hydrogen atom, an optionally substituted alkyl group, or an optionally substituted alkoxy group.) The solvent (C) is at least one solvent selected from the group consisting of water and alcohols.

[0029] The water-repellent paint of the present invention preferably further contains (D) a hydrolysis product of an alkoxysilane.

[0030] The water-repellent paint of the present invention preferably contains (E) silver.

[0031] The water-repellent paint of the present invention preferably has a water contact angle of 130° or more after being applied to a glass substrate.

[0032] The water-repellent coating of the present invention preferably contains, (A) The Ti compound has a content of 0.01% to 5% by mass, (B) Fluorine-free Si compounds have a content of 0.01% to 20% by mass.

[0033] In the water-repellent coating of the present invention, preferably, the hydrolysis product of (D) alkoxysilane is the hydrolysis product of tetraethyl orthosilicate (TEOS).

[0034] The present invention encompasses an antibacterial and antiviral coating liquid containing the water-repellent coating of the present invention.

[0035] The water-repellent coating of the present invention is a non-fluorine-based coating having a high water-repellent coating with a contact angle of 130° or more.

[0036] (1-1)(A)Ti compound The water-repellent coating of the present invention contains (A)Ti compound, and the average primary particle size of the (A)Ti compound is 1 nm to 50 nm.

[0037] Water, inorganic acids, and liberated organic acids generally evaporate almost completely below 200°C.

[0038] (A) The titania compound (titania nanoparticles) of the Ti compound (preferably titania-coated silver) has acetyl groups (CH3-C(=O)-, Ac), acetoxy groups (acetyloxy group, CH3-C(=O)-O-, AcO), etc. bonded to at least some of the titanium atoms present on its surface, and these gradually detach in the range of 200°C to 600°C. For example, in the case of acetoxy groups, they gradually detach in the range of 200°C to 600°C, with a peak at approximately 260°C.

[0039] Titania compounds can improve the dispersibility of titania particles by imparting organic matter to the fine titania surface. Preferably, the titania compound has organic chains such as acetyl groups and acetoxy groups bonded to at least some of the titanium atoms on its surface, which suppresses aggregation of titania nanoparticles during drying or firing, making it less prone to cracking and peeling, and resulting in excellent coatability and transparency. Because the titania compound can suppress cracking and peeling and easily support metals, it also exhibits excellent visible photocatalytic activity.

[0040] Titania compounds are particularly effective at suppressing cracks and peeling because they can inhibit the aggregation of titania nanoparticles during drying or calcination.

[0041] Titania compounds, when at least some of the titanium atoms on their surface have organic chains such as acetyl groups or acetoxy groups, gradually detach in the range of 200°C to 600°C. Therefore, when heated, differential thermogravimetric analysis (TG-DTA) shows a large mass loss above 200°C.

[0042] For titania compounds, the mass loss at temperatures above 200°C, as measured by differential thermogravimetric analysis (TG-DTA), indicates the number of organic chains, such as acetyl groups and acetoxy groups, bonded to titanium atoms on the surface.

[0043] In water-repellent coatings, the titanium (Ti) compound contained in (A)Ti compound preferably exhibits a mass loss of 1% by mass or more at temperatures above 200°C when the Ti compound is heated to 600°C using a differential thermogravimetric analyzer (TG-DTA). The mass loss of the Ti compound at temperatures above 200°C when heated to 600°C using a differential thermogravimetric analyzer (TG-DTA) is 0.1% by mass or more, preferably 1% by mass or more, and more preferably 5% by mass or more. The upper limit of the mass loss of the Ti compound is preferably 20% by mass.

[0044] The detailed conditions for the differential thermogravimetric simultaneous thermometry device (TG-DTA) are: atmosphere: air, heating rate: 3°C / min.

[0045] The organic chains (acetyl groups, acetoxy groups, etc.) present on the surface of the Ti compound are preferably acetyl groups (CH3-C(=O)-), acetoxy groups (CH3-C(=O)-O-), etc., from the viewpoint of water solubility, odor, volatility, harmfulness, and decomposability.

[0046] The organic chain may have at least one organic chain selected from the group consisting of the aforementioned organic chains attached to it. These organic chains may be attached individually, or two or more organic chains may be attached depending on the purpose.

[0047] In water-repellent coatings, the average primary particle size of the (A)Ti compound is 1 nm to 50 nm, preferably 1 nm to 20 nm, and more preferably 1 nm to 10 nm. By adjusting the average primary particle size of the Ti compound to this range, it becomes possible to partially coat the silver with Ti. Titania nanoparticles can form a film with higher visible photocatalytic activity and higher transparency. The Ti compound has excellent coatability.

[0048] The average primary particle size of the Ti compound (titania nanoparticles) is measured by electron microscopy (TEM) observation. The average primary particle size is calculated as follows:

[0049] First, adjust the magnification of the electron microscope to a level where the particles are clearly visible and take an image. Load the captured image into image processing software such as WINROOF. Then, use the shape measurement function to evaluate the shape of the particles. The resulting equivalent circle diameter (Heywood diameter) is defined as the particle diameter of that particle. Perform this operation on any 20 particles and define the average as the average primary particle diameter.

[0050] The specific surface area of ​​the Ti compound is preferably 150 m². 2 / g~500m 2 It is / g, more preferably 200m 2 / g~400m 2The value is / g. By adjusting the specific surface area of ​​the Ti compound to this range, it is possible to coat the Ti compound with metals (silver and copper) to an appropriate degree, partially coating the silver with Ti. The Ti compound exhibits high visible photocatalytic activity.

[0051] The specific surface area of ​​the Ti compound is measured by the BET method.

[0052] The concentrations of N, Cl, and S in the Ti compound can be preferably 0 to 5,000 ppm, more preferably 0 to 1,000 ppm. By adjusting the concentrations of N, Cl, and S in the Ti compound to this range, corrosion of the substrate can be suppressed. The concentrations of N, Cl, and S in the Ti compound mean that impurities derived from acidic Ti compound precursors such as TiCl4 and TiOSO4 are absent or present in very small amounts.

[0053] The concentrations of N, Cl, and S elements in Ti compounds are measured by WDX (X-ray fluorescence).

[0054] The crystalline form of the Ti compound is preferably the anatase form. The Ti compound (titania nanoparticles) is preferably the anatase form, more preferably a crystalline form containing 90% or more of the anatase form, and even more preferably a crystalline form that contains no crystalline forms other than the anatase form and is 100% anatase form. By using the anatase form of the Ti compound, the visible photocatalytic activity of the Ti compound is improved.

[0055] (1-2)(E) Silver The water-repellent coating of the present invention preferably further contains (D) silver. In the water-repellent coating, the (A)Ti compound preferably has a structure in which a titania compound is supported around (D) silver fine particles (carrier), or a structure in which titania coats the silver fine particles (carrier) (titania-coated silver).

[0056] (1-3) (B) Fluorine-free Si compounds The water-repellent coating of the present invention contains (B) a fluorine-free Si compound, and (B) the fluorine-free Si compound is a compound represented by the following formula (1). CH3-(CH2) a -Si(R 1 )(R 2 )(R 3 ) (1) In equation (1), a represents an integer between 3 and 30. In formula (1), R 1 , R 2 , and R 3 These terms, whether identical or different, represent a hydrogen atom, an optionally substituted alkyl group, or an optionally substituted alkoxy group, respectively.

[0057] (B) The fluorine-free Si compound is more preferably the compound represented by formula (1), and can impart water repellency to water-repellent coatings. In water-repellent coatings, the fluorine-free Si compound (B) undergoes hydrolysis on the titania surface, exposing hydrophobic groups to the surface and improving the water repellency of the water-repellent coating.

[0058] (B) Fluorine-free Si compounds are more preferably hexyltrimethoxysilane, octyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, hexadecyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, dodecyltriethoxysilane, octadecyltriethoxysilane, hexadecyltriethoxysilane, etc.

[0059] (B) The fluorine-free Si compound may be at least one compound selected from the group consisting of the above compounds, and these compounds may be used individually or two or more may be mixed (blended) depending on the purpose.

[0060] (1-4)(C) Solvent The water-repellent coating of the present invention comprises (C) a solvent, where (C) is at least one solvent selected from the group consisting of water and alcohols.

[0061] The alcohols are preferably aliphatic alcohols having 1 to 6 carbon atoms such as methanol, ethanol, propanol, and isopropanol, and non-aliphatic alcohols such as α-terpineol; glycol solvents such as butyl carbitol (diethylene glycol monobutyl ether), hexylene glycol (2-methyl-2,4-pentanediol), ethylene glycol-2-ethylhexyl ether, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether; and diols such as 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.

[0062] The alcohol may be at least one compound selected from the group consisting of the aforementioned alcohols, and these alcohols may be used individually or mixed (blended) with two or more depending on the purpose.

[0063] In water-repellent coatings, it is also possible to change the solvent. The water-repellent coating can be removed from the reaction solution by centrifugal separation, filtration, etc., and replaced with an organic solvent.

[0064] (1-5)(D) Hydrolysis products (binders) of alkoxysilanes The water-repellent coating of the present invention preferably comprises (D) a hydrolysis product (binder) of an alkoxysilane (alkylsilane).

[0065] Water-repellent coatings contain Ti compounds (titania particles), and by applying organic matter to the fine titania surface, the dispersibility of the titania particles can be improved. By mixing Ti compounds (titania particles) with alkoxysilane, which is a raw material for the hydrolysis product (binder) of (D) alkoxysilane, and allowing the two to coexist, a titania particle composite binder can be produced by carrying out a hydrolysis reaction while maintaining high dispersibility. Water-repellent coatings can improve the aggregation of titania, and can greatly improve solvent stability and adhesion.

[0066] The alkoxysilane is preferably trialkoxysilane, and more preferably methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltriisopropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltripropoxysilane, ethyltriisopropoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-propyltripropoxysilane, n-propyltriisopropoxysilane, isopropyltrimethoxysilane, isopropyltrimethoxysilane, isopropyltripropoxysilane, n-butyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-octyltriethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, etc.

[0067] More preferably, the alkoxysilane used is methyltrimethoxysilane, methyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, etc.

[0068] The alkoxysilane is preferably a tetraalkoxysilane, and more preferably a tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, etc.

[0069] More preferably, the alkoxysilane used is tetraethoxysilane (tetraethyl orthosilicate, Si(OC2H5)4, TEOS), tetramethoxysilane, etc.

[0070] The alkoxysilane may be at least one compound selected from the group consisting of the aforementioned alkoxysilanes, and these alkoxysilanes may be used individually or two or more may be mixed (blended) depending on the purpose.

[0071] In water-repellent coatings, the hydrolysis product of (D) alkoxysilane is particularly preferably the hydrolysis product of TEOS (tetraethyl orthosilicate, tetraethoxysilane).

[0072] (1-6) Water-repellent paint In the water-repellent coating of the present invention, preferably, the (A)Ti compound is contained in a content of 0.01% to 5% by mass.

[0073] The water-repellent coating of the present invention preferably contains (B) a fluorine-free Si compound with a content of 0.01% to 20% by mass.

[0074] (1-7) Contact angle of water-repellent coatings The water-repellent coating of the present invention preferably has a water contact angle of 60° or more after being applied to a substrate, more preferably 90° or more, and even more preferably 130° or more. Because the water-repellent coating has a contact angle of 60° or more, the coating film formed from the water-repellent coating exhibits excellent water repellency, antifouling properties, etc. In order for the coating film formed from the water-repellent coating of the present invention to exhibit good water repellency, antifouling properties, etc., a higher contact angle is generally preferable.

[0075] The contact angle (°) is measured using a water-repellent coating (coating composition, dispersion) and a contact angle meter (DM400) manufactured by Kyowa Interface Science Co., Ltd., in accordance with JIS R 3257.

[0076] (1-8) Water-repellent paint, antibacterial and antiviral coating liquid, and coating film In the water-repellent coating of the present invention, the dispersibility of the titania particles can be improved by applying organic matter to the fine titania surface. By mixing the titania compound (titania particles) with an alkoxysilane, which is a raw material for the binder, and carrying out a hydrolysis reaction while maintaining high dispersibility through the coexistence of the two, a titania particle composite binder can be produced.

[0077] Water-repellent coatings can improve titania aggregation, significantly improving the solvent stability of the coating and the adhesion of the coating film. Due to their good dispersibility, water-repellent coatings offer superior crack resistance. They also enable dense titania coatings, providing excellent applicability, transparency, and visible photocatalytic activity.

[0078] In water-repellent coatings, the content of (A)Ti compound is preferably 0.01% to 5% by mass in the composition, from the viewpoint of ease of coating and film properties of the coating.

[0079] In water-repellent coatings, the content of (B) fluorine-free Si compounds is preferably 0.01% to 20% by mass in the composition, from the viewpoint of ease of coating and film properties of the coating.

[0080] In water-repellent coatings, the ratio of (A) Ti compound to (B) fluorine-free Si compound in the composition is preferably such that, from the viewpoint of ease of coating and film properties of the coating, (A) Ti compound is present in a mass ratio of 0.02 to 20 (0.02 to 20 parts by mass) per (1 part by mass) of (B) fluorine-free Si compound, and more preferably, (A) Ti compound is present in a mass ratio of 0.1 to 1 (0.1 to 1 part by mass).

[0081] The pH of the water-repellent coating (dispersion) varies depending on the type and amount of metal added, and from the viewpoint of coatability, it is preferably 1 to 5, and more preferably 2 to 4.

[0082] The present invention encompasses an antibacterial and antiviral coating liquid containing the water-repellent coating of the present invention.

[0083] The water-repellent coating of the present invention is preferably prepared by adjusting its viscosity according to its intended use. When the coating is applied by spin coating, dip coating, spraying, etc., it is preferably prepared to have a low viscosity. When the coating is applied by brushing, squeegeeing, etc., it is preferably prepared to have a higher viscosity. When the coating is applied by screen printing, it is preferably prepared to have an even higher viscosity to suppress fluidity.

[0084] The coating film formed by the antibacterial and antiviral coating liquid containing the water-repellent paint of the present invention enables a dense coating.

[0085] The present invention includes an antibacterial and antiviral coating film (coating film) formed by an antibacterial and antiviral coating liquid containing the water-repellent coating of the present invention.

[0086] Painted products having a coating film are not particularly limited and include, for example, building materials, building exteriors, building interiors, window frames, window glass, various lenses, structural members, building equipment such as houses, cooking utensils, textile products, furniture, displays, display protective films, plumbing components, covers and window glass for vehicle lighting, machinery or exteriors of articles, dust covers and coatings, display equipment and their covers, traffic signs, various display devices, advertising towers and other display objects, sound barriers for roads and railways, bridges, guardrail exteriors and coatings, tunnel interiors and coatings, insulators, solar cell covers, solar water heater collector covers and other exterior parts of electronic and electrical equipment used outdoors, especially transparent members, vinyl greenhouses, greenhouses and the like.

[0087] [2] Method for manufacturing water-repellent coatings The method for producing the water-repellent coating of the present invention is a method for producing the water-repellent coating of the present invention. (1) A step of synthesizing a Ti compound in a solvent, attaching an organic chain to the Ti compound, and then producing titania-coated silver, and (2) After step (1), the process includes mixing the titania-coated silver to which the organic chain is attached, a fluorine-free Si compound, and an alkoxysilane in a solvent, and then hydrolyzing the fluorine-free Si compound and the alkoxysilane.

[0088] The method for producing the water-repellent coating of the present invention is preferably, (3) After step (2), the process includes a step of performing a high-pressure dispersion treatment to disperse the dispersion containing titania-coated silver.

[0089] Titania-coated silver is a material in which a portion of the surface of silver (Ag) nanoparticles is coated with titania.

[0090] (2-1) (1) A step of synthesizing a Ti compound in a solvent, attaching an organic chain to the Ti compound, and then producing titania-coated silver. In the method for manufacturing the water-repellent coating of the present invention, first, organic matter is applied to the surface of fine titania to improve the dispersibility of titania particles.

[0091] (A Ti compound is synthesized in a solvent, and an organic chain is added to the Ti compound.) In step (1), organic chains are bonded to the surface of the Ti compound in a solvent.

[0092] The Ti compound (a substance containing titanium) is preferably a substance that becomes titanium oxide upon heating. The titanium-containing substance is preferably titanium oxide and / or a titanium oxide precursor, and more preferably titanium oxide; titanium hydroxide; titanium alkoxide; titanium halides such as titanium trichloride and titanium tetrachloride (especially those neutralized with a base); or metallic titanium.

[0093] From the viewpoint of the dispersibility, coatability, and visible photocatalytic properties of the resulting titania, the titanium-containing substance is preferably titanium alkoxide, titanium hydroxide, or titanium halide (especially those neutralized with a base). From the viewpoint of purity, dispersibility, coatability, transparency, and visible photocatalytic properties, the titanium-containing substance is more preferably titanium alkoxide.

[0094] The titanium alkoxide is preferably titanium tetraisopropoxide, titanium tetra-n-butoxide, titanium tetra-n-propoxide, or titanium tetraethoxide. From the viewpoint of cost, water solubility of by-products, applicability, and visible photocatalytic properties, titanium tetraisopropoxide is more preferable.

[0095] The Ti compound may be at least one compound selected from the group consisting of the aforementioned Ti compounds, and these Ti compounds may be used individually or two or more may be mixed (blended) depending on the purpose.

[0096] The average primary particle size of the Ti compound is preferably 100 nm or less, and more preferably 50 nm or less. There is no specific lower limit set for the average primary particle size of the titanium-containing material, but it is preferably about 1 nm. If the particle size is large, it is preferably ground dry or wet using a planetary ball mill, paint shaker, etc.

[0097] The average primary particle size of Ti compounds (solids such as titanium oxide, metallic titanium, and titania nanoparticles) is measured by electron microscopy (TEM). The average primary particle size is calculated as follows:

[0098] First, adjust the magnification of the electron microscope to a level where the particles are clearly visible and take an image. Load the captured image into image processing software such as WINROOF. Then, use the shape measurement function to evaluate the shape of the particles. The equivalent circle diameter (Heywood system) calculated therein is defined as the particle diameter of the particle. Perform this operation on any 20 particles and define the average as the average primary particle diameter.

[0099] The concentration of the Ti compound in the dispersion is preferably 0.01 mol / L to 5 mol / L, and more preferably 0.05 mol / L to 3 mol / L, from the viewpoint of productivity, viscosity of the reaction solution, coatability, transparency, and visible photocatalytic properties.

[0100] The acid used in the reaction is an organic acid, and a volatile acid is preferred; therefore, a chemical formula C is preferred. n H 2n+1 Monocarboxylic acids represented by COOH(n=0~3) (monocarboxylic acids with 1 to 4 carbon atoms), hydroxycarboxylic acids with 2 to 3 carbon atoms, etc. are used.

[0101] From the viewpoint of volatility, toxicity, and degradability, the monocarboxylic acids are preferably formic acid with n=0 and acetic acid with n=1.

[0102] The hydroxycarboxylic acid is preferably glycolic acid, lactic acid, etc., and more preferably acetic acid, glycolic acid, lactic acid, etc., from the viewpoint of water solubility and odor.

[0103] The organic acid may be at least one compound selected from the group consisting of the aforementioned organic acids, and these organic acids may be used individually or two or more may be mixed (blended) depending on the purpose.

[0104] The amount of organic acid used is adjusted so that, from the viewpoint of dispersibility, coatability, transparency, visible photocatalytic properties, and cost, the number of moles of acyloxy groups in the Ti compound is preferably 1.5 moles or more, and particularly preferably 2 moles or more, per mole of titanium. The more organic acid used, the better the long-term stability, coatability, transparency, etc. can be improved. There is no particular upper limit to the amount of organic acid used, but it is preferably adjusted so that the number of moles of acyloxy groups in the Ti compound is 10 moles or less per mole of titanium.

[0105] The concentration of the organic acid in the dispersion is preferably 0.02 mol / L to 10 mol / L, and more preferably 0.1 mol / L to 7 mol / L, from the viewpoints of dispersibility, coatability, transparency, visible photocatalytic properties, and cost.

[0106] The reaction solvent is preferably an aqueous solvent such as water, mainly composed of (preferably 50% by mass or more). The reaction solvent may also contain alcohol or ester during the reaction.

[0107] When titanium tetraisopropoxide is used as the reaction solvent, isopropyl alcohol is produced by reaction with organic acids. Isopropyl esters of organic acids may be produced by heating. Alcohols or esters may be added to the dispersion, or they may be generated in the system. Alcohols or esters may be removed by heating in an open system below 100°C, by reducing the pressure, or they may remain in the reaction solution.

[0108] When alcohol is present in the dispersion, the average primary particle size of the resulting Ti compound (titania nanoparticles) tends to decrease. Therefore, alcohol may be intentionally added to control the average primary particle size.

[0109] The pH of the dispersion is preferably 2 or higher and less than 6, and more preferably 2.1 to 5, from the viewpoint of preventing corrosion of the equipment, ensuring safety during handling, and maintaining dispersibility.

[0110] The method for preparing the dispersion is not particularly limited; the Ti compound, organic acid, and water (solvent) may be mixed simultaneously or sequentially. In mass production, from the viewpoint of preventing aggregation and the formation of large clumps, and facilitating continued stirring, it is preferable to mix the organic acid and water (solvent) first, and then add the titanium-containing substance while stirring. In laboratory scale, it is preferable to mix the titanium-containing substance and the organic acid first, and then add the water while stirring.

[0111] (Preparing titania-coated silver) Titania-coated silver is produced by irradiating a composite of a Ti compound and a silver compound with ultraviolet light. In the water-repellent coating of the present invention, (A) the Ti compound preferably has a structure in which a titania compound is supported around silver nanoparticles (carrier), or a structure in which titania coats the silver nanoparticles (carrier) (titania-coated silver).

[0112] High-pressure dispersion method (pressure treatment) It is desirable to disperse Ti compounds (titania compounds) using a dispersion device that generates high pressure through collisions between particles to disperse them. For example, this can be done with a jet mill, and by doing so, titania particles can be highly dispersed in a liquid, making it possible to partially coat the material with titania.

[0113] A dispersion containing a Ti compound (preferably titania fine particles) is subjected to a pressure treatment of 30 MPa or higher (high-pressure dispersion method).

[0114] The Ti compound becomes finer when subjected to pressure treatment.

[0115] The pressure level during the pressurization treatment is not particularly limited, as long as it is sufficient to adequately atomize the Ti compound. Preferably, the pressure level is adjusted to 30 MPa or higher, more preferably to 50 MPa to 400 MPa, and even more preferably to 100 MPa to 300 MPa. The pressurization treatment is preferably carried out using a high-pressure dispersion device. A high-pressure dispersion device can disperse the Ti compound by applying mechanical pressure.

[0116] By pressurizing, for example, (i) Colliding two or more dispersions of Ti compounds with each other, (ii) Colliding a dispersion of a Ti compound with a metal or ceramic material (high-hardness material such as silicon carbide or alumina), (iii) Dispersion of Ti compound with a cross-sectional area of ​​1 cm² 2 Passing through the following space Perform processes such as those described above.

[0117] By applying pressure, it is possible to increase the pressure conditions, which allows for more efficient atomization of Ti compounds and further reduces processing time.

[0118] The pressurization operation is preferably performed once or more times, and more preferably 10 times or more.

[0119] The pressurizing temperature is not particularly limited. The pressurizing temperature is adjusted to a temperature that allows for sufficient thinning of the carbonaceous material having a layered structure. The pressurizing temperatures in (i) and (ii) are preferably adjusted to 0°C to 100°C, more preferably to 20°C to 95°C. When mechanically applying pressure, the pressurizing temperature in (iii) is preferably adjusted to 0°C to 100°C. When pressure is generated by a supercritical state of water, the pressurizing temperature in (iii) is preferably adjusted to 373°C to 700°C, more preferably to 380°C to 450°C.

[0120] When performing pressurized treatment, it is preferable to perform ultrasonic dispersion treatment on the dispersion containing the Ti compound as a preliminary treatment (pretreatment) to atomize the Ti compound. This can have effects such as preventing clogging in high-pressure dispersion devices, supercritical water production devices, etc.

[0121] The output power during ultrasonic dispersion treatment is not particularly limited. From the viewpoint of atomizing the Ti compound, the output power during ultrasonic dispersion treatment is preferably adjusted to be stronger than that of typical ultrasonic dispersion treatment (approximately 40W to 50W). The output power of the ultrasonic dispersion treatment is preferably adjusted to 100W or more, more preferably to 300W to 20,000W, and even more preferably to 400W to 18,000W.

[0122] The ultrasonic dispersion temperature is not particularly limited. Preferably, the ultrasonic dispersion temperature is adjusted to a temperature that allows for sufficient atomization of the Ti compound. Preferably, the ultrasonic dispersion temperature is adjusted to 0°C to 80°C, and more preferably to 10°C to 70°C.

[0123] The ultrasonic dispersion time is not particularly limited. Preferably, the ultrasonic dispersion time is adjusted to a time that allows for sufficient atomization of the Ti compound. Preferably, the ultrasonic dispersion time is adjusted to 1 minute to 600 minutes, and more preferably to 3 minutes to 120 minutes.

[0124] These processes may be pre-processed or post-processed by other dispersion devices, such as conventional mechanical stirring, dispersion using an emulsifier, or dispersion using a bead mill.

[0125] UV light irradiation Ultraviolet (UV) light irradiation is preferably carried out at room temperature (below 20°C), more preferably at 15°C or below, from the viewpoint of ease of supporting silver on the Ti compound (titania nanoparticles) (titania-coated silver), visible photocatalytic activity, reaction rate, productivity, controllability of aspect ratio, resistance to discoloration during low-intensity UV irradiation, visibility during high-intensity UV irradiation, and re-transparency in UV-free environments. The lower limit of the UV light irradiation temperature is not particularly limited, but is preferably 0°C when reacting at atmospheric pressure. When UV light irradiation is carried out, stirring is preferably performed from the viewpoint of ensuring sufficient reaction between the dispersion and the silver salt. The method of stirring is not particularly limited and can be carried out according to conventional methods.

[0126] The reaction time for ultraviolet light irradiation is preferably 1.5 hours or more, and more preferably in the range of 1.5 hours to 36 hours. By adjusting the reaction time to 1.5 hours or more, inorganic oxide fine particles are well supported around the silver nanoparticles, and gelation of the silver nanoparticles does not occur. By adjusting the reaction time to within 36 hours, the particle size of the silver nanoparticles is adjusted, and precipitation of the silver nanoparticles does not occur.

[0127] From the viewpoint of ease of loading, reaction rate, reaction controllability, and productivity, an ultraviolet irradiation device containing wavelengths of 280 nm to 500 nm is preferably used. By adjusting the wavelength of the ultraviolet light to a range of 280 nm or higher, the dispersion stability of titania-coated silver is good. By adjusting the wavelength of the ultraviolet light to a range of 500 nm or lower, the silver is well reduced and silver nanoparticles are well generated.

[0128] Preferably, the composition of the present invention further contains at least one metal selected from the group consisting of silver, copper, and platinum.

[0129] When using a silver salt as the silver compound, the silver salt is preferably an acidic or neutral silver salt in aqueous solution. Preferably, the silver salt is silver(I) chloride, silver(I) nitrate, silver organic acid (silver(I) lactate, silver(I) acetate, silver(I) citrate, silver(I) myristate, etc.), silver(I) sulfide, silver(I) oxide, silver(I) phosphate, silver(I) carbonate, silver(I) bromide, silver(I) iodide, etc. The silver salt may be at least one compound selected from the group consisting of the above silver salts, and these silver salts may be used individually or mixed (blended) with two or more depending on the purpose.

[0130] The amount of silver salt used is preferably 50% by mass or less relative to the titanium oxide in the Ti compound (titania nanoparticles), more preferably 0.01% to 40% by mass, and even more preferably 0.01% to 25% by mass, based on the mass of silver element in the silver salt, from the viewpoint of dispersibility, transparency, antimicrobial activity (antimicrobial activity and antiviral activity), and stability of the Ti compound (titania nanoparticles). By adjusting the amount of silver salt used within this range, it is possible to easily maintain coatability and transparency, and to particularly improve antimicrobial activity, antiviral activity, and photocatalytic activity in the dark.

[0131] Titania-coated silver can be recovered by conventional methods, such as precipitation and centrifugation. Organic chains are bonded to titanium atoms present on the surface, and (A) titania-coated silver has a structure in which a titania compound is supported around silver nanoparticles (carriers), or a structure in which titania coats the silver nanoparticles (carriers).

[0132] (2-2)(2) After step (1), the titania-coated silver to which the organic chain is attached, a fluorine-free Si compound, and an alkoxysilane are mixed in a solvent, and then the fluorine-free Si compound and the alkoxysilane are hydrolyzed. In step (2), the titania-coated silver with organic chains attached is mixed with a fluorine-free Si compound in a solvent, and the fluorine-free Si compound is hydrolyzed (preparation of coating solution).

[0133] In the manufacturing process, titania particles and alkoxysilane, which is a raw material for the binder, are mixed together. By maintaining high dispersibility through the coexistence of the two, a hydrolysis reaction is carried out to produce a titania particle composite binder.

[0134] Hydrolysis is preferably carried out by covering the dispersion with a lid to prevent the solvent from evaporating and maintaining the dispersion at a temperature of about 65°C for about 15 hours.

[0135] Hydrolysis is preferably carried out under normal pressure or under pressure in a sealed container.

[0136] The pH of the dispersion is preferably 2 or higher and less than 6, and more preferably 2.1 to 5, from the viewpoint of preventing corrosion of the equipment, ensuring safety during handling, and maintaining dispersibility.

[0137] In titania-coated silver, organic substances (acetyl groups, acetoxy groups, etc.) bonded to the surface of the Ti compound (titania) react with fluorine-free Si compounds, and the hydrolysis of the fluorine-free Si compound proceeds (hydrolyzed product), resulting in a transparent coating solution.

[0138] (2-3)(3) After step (2), a high-pressure dispersion treatment is performed to disperse the dispersion containing titania-coated silver. Preferably, the coating liquid can be subjected to high-pressure dispersion treatment (high-pressure dispersion method) to obtain a transparent dispersion.

[0139] The manufacturing method of the present invention, by producing a composition containing titania particles through a novel process, can improve the aggregation of titania, which has been a problem in the past, and can greatly improve solvent stability and adhesion. [Examples]

[0140] The present invention will be specifically described below with reference to examples.

[0141] The present invention is not limited to the following specific embodiments.

[0142] [1] Manufacturing of water-repellent coatings [Example 1] (Step 1) Method for preparing photocatalytic titanium dioxide 70 g of titanium tetraisopropoxide was mixed with 15 g of acetic acid and stirred. Then, water was added until the total volume reached 400 g, and the mixture was stirred for 90 minutes. The reaction mixture was then heated to 98°C and stirred with a hot stirrer for 9 hours to obtain a homogeneous titania sol. The obtained sol was subjected to ultrasonic dispersion for 30 minutes to obtain a transparent titania sol.

[0143] The TG-DTA of the obtained titania sol was measured after heating it to 600°C under an air atmosphere at a rate of 3°C / min. The mass loss rate above 200°C was 10% by mass. This mass loss rate above 200°C is due to organic matter derived from acetic acid bound to the titania surface. To adjust the concentration of the obtained titania sol, it was diluted with water to obtain a titania sol with a TiO2 concentration of 2% by mass (wt%).

[0144] When the particle size of the obtained titania sol was observed by TEM, the average primary particle size was found to be 5 nm.

[0145] (Step 2) Compounding with metal ions To the titania sol prepared as described above, with a TiO2 concentration of 2% by mass, silver nitrate was added so that the weight ratio of Ag / TiO2 was 0.01, and the mixture was thoroughly stirred until the whole was homogeneous. Next, the titania sol was irradiated with an ultraviolet lamp for 24 hours to reduce the silver nitrate and obtain a silver-compound titania sol.

[0146] (Step 3) Preparation of coating solution To 120 g of the 2% by mass silver-compound titania sol prepared as described above, 0.6 g of tetraethyl orthosilicate (TEOS) and 2.4 g of hexyltrimethoxysilane were added. Then, ethanol was added until the total volume reached 300 g. After that, the reactor was covered to prevent the solvent in the reaction solution from evaporating, and the mixture was maintained at 60°C for 1 hour. The organic matter bound to the titania surface reacted with tetraethyl orthosilicate and hexyltrimethoxysilane, and the hydrolysis of tetraethyl orthosilicate and hexyltrimethoxysilane proceeded, yielding a transparent coating solution.

[0147] The obtained liquid was subjected to high-pressure dispersion treatment (high-pressure dispersion method), and a clear dispersion was obtained.

[0148] [Example 2] In Example 2, the coating solution was prepared using the same process as in Example 1, except that in step 3 of Example 1, hexyltrimethoxysilane was replaced with octyltrimethoxysilane.

[0149] [Example 3] Example 3 was prepared using the same process as in Example 1, except that in step 3 of Example 1, hexyltrimethoxysilane was replaced with hexadecyltrimethoxysilane.

[0150] [Example 4] Example 4 was prepared using the same process as in Example 1, except that in step 3 of Example 1, hexyltrimethoxysilane was replaced with octadecyltrimethoxysilane.

[0151] [Example 5] Example 5 was prepared using the same process as in Example 1, except that the amount of hexyltrimethoxysilane added in step 3 of Example 1 was changed to 0.6 g.

[0152] [Example 6] Example 6 was prepared using the same process as in Example 1, except that in step 3 of Example 1, the amount of titania sol added was changed to 240 g and the amount of hexyltrimethoxysilane added was changed to 4.8 g.

[0153] [Example 7] Example 7 was prepared using the same process as in Example 1, except that in step 3 of Example 1, the amount of titania sol added was changed to 15 g and the amount of hexyltrimethoxysilane added was changed to 0.3 g.

[0154] [Comparative Example 1] Comparative Example 1 involved adding 0.6 g of Builddeck (manufactured by Dainippon Paint Co., Ltd.), an acrylic resin and paint, and 2.4 g of hexyltrimethoxysilane to 120 g of 2% by mass silver composite titania sol as in Example 1, and then adding ethanol until the total volume reached 300 g. Otherwise, the coating solution was prepared using the same process as in Example 1.

[0155] [2] Evaluation of water-repellent coatings The following evaluations were performed on the coating solutions (water-repellent coatings) obtained in the examples and comparative examples.

[0156] (1) Dispersibility (stability) of the dispersion The coating solution (dispersion) was allowed to stand at 60°C for 480 hours. After standing, the dispersion was visually inspected and its dispersion stability was evaluated.

[0157] The criteria for evaluating the coating solution are as follows: ◎: No precipitation, gelation, or other phenomena are observed in the dispersion. ○: Separation is observed in the dispersion, but it disperses easily by stirring by hand. △: Separation is observed in the dispersion, but it can be redispersed by applying external force such as ultrasound. ×: Precipitation and gelation have occurred in the dispersion, and it will not redisperse.

[0158] (2) Contact angle measurement A glass substrate was used as the coating base material, and the coating solution was applied to the glass substrate using a spin coater at a rotation speed of 1,000 rpm. The contact angle (°) was measured using the coating solution (dispersion) with a contact angle meter (DM400) manufactured by Kyowa Interface Science Co., Ltd., in accordance with JIS R 3257.

[0159] (3) Antiviral test After drying, the coating solution (dispersion) was subjected to antiviral testing in the dark using Qβ phage (non-enveloped virus) in accordance with ISO 21702.

[0160] The criteria for determining the antiviral properties of the coating solution are as follows: ◎: The dispersion has an antiviral activity value of 2 or higher. ×: The dispersion has an antiviral activity value of less than 2.

[0161] The results of the examples and comparative examples are shown in the table below.

[0162] [Table 1]

[0163] In Examples 1 to 7, coating solutions were obtained that exhibited excellent dispersion stability, water repellency (contact angle of the dispersion), and antiviral properties (water-repellent coatings).

[0164] In Comparative Example 1, the coating solution exhibited precipitation, poor dispersion stability, a contact angle of 54°, and low water repellency.

[0165] [Industrial applicability] The present invention relates to a water-repellent coating with a high water-repellent coating having a contact angle of 130° or more, in a non-fluorine composition.

Claims

1. It is a water-repellent paint, (A) Ti compounds and (B) Si compounds that do not contain fluorine and (C) Contains a solvent, The (A)Ti compound has an average primary particle diameter of 1 nm to 50 nm. The aforementioned (B) fluorine-free Si compound is a compound represented by the following formula (1): CH 3 -(CH 2 ) a -Si(R 1 )(R 2 )(R 3 ) (1) (In equation (1), a represents an integer between 3 and 30.) In formula (1), R 1 , R 2 , and R 3 are identical or different and each independently represents a hydrogen atom, an optionally substituted alkyl group, or an optionally substituted alkoxy group.) The solvent (C) is at least one solvent selected from the group consisting of water and alcohols. Water-repellent paint.

2. Furthermore, the water-repellent coating according to claim 1, further comprising (D) a hydrolysis product of an alkoxysilane.

3. Furthermore, the water-repellent coating according to claim 1, further comprising (E) silver.

4. The water-repellent coating is the water-repellent coating according to any one of claims 1 to 3, wherein the water-contact angle after application to a glass substrate is 130° or more.

5. Among water-repellent coatings, The (A)Ti compound has a content of 0.01% to 5% by mass, The aforementioned (B) fluorine-free Si compound has a content of 0.01% to 20% by mass. A water-repellent coating according to any one of claims 1 to 3.

6. The hydrolysis product of (D) alkoxysilane is a hydrolysis product of tetraethyl orthosilicate (TEOS), as described in claim 2.

7. An antibacterial and antiviral coating liquid comprising the water-repellent paint described in any one of claims 1 to 3.

8. A method for manufacturing a water-repellent coating according to any one of claims 1 to 3, (1) A step of synthesizing a Ti compound in a solvent, attaching an organic chain to the Ti compound, and then producing titania-coated silver, and (2) After step (1), the titania-coated silver to which the organic chain is attached, a fluorine-free Si compound and an alkoxysilane are mixed in a solvent, and then the fluorine-free Si compound and the alkoxysilane are hydrolyzed. A method for manufacturing water-repellent coatings, including [the specified element].

Citation Information

Patent Citations

  • Water repellent-oil repellent coating article and production of the same

    JP2010089373A

  • Compositions containing titania-coated silver

    JP7574486B1